Cognitive Function Predicts Weight Loss Following Bariatric Surgery - Spitznagel, Mary Beth (2011)
BACKGROUND: Clinically significant cognitive impairment is found in a subset of patients undergoing bariatric surgery. These difficulties could contribute to reduced adherence to postsurgical lifestyle changes and decreased weight loss. OBJECTIVES: The current study is the first to prospectively examine the independent contribution of cognitive function to weight loss following bariatric surgery. Executive function/attention and verbal memory at baseline were expected to negatively predict percent excess weight loss (%EWL) and body mass index (BMI) at follow-up. SETTING: Three sites of the Longitudinal Assessment of Bariatric Surgery (LABS) parent project were used: Columbia, Cornell, and Neuropsychiatric Research Institute METHODS: Eighty-four individuals enrolled in the LABS project undergoing bariatric surgery completed cognitive evaluation at baseline. BMI and %EWL were calculated at 12-week and 12-month post-surgery follow-ups. RESULTS: Clinical impairment in task performance was most prominent in tasks associated with verbal recall and recognition (14.3–15.5% of the sample) and perseverative errors (15.5%). After accounting for demographic and medical variables, baseline tests of attention/executive function and memory predicted BMI and %EWL at 12 months, but not at 12 weeks. CONCLUSIONS: Results demonstrate that baseline cognition predicts greater %EWL and lower BMI 12 months following bariatric surgery. Further work is needed to clarify the degree to which cognition contributes to adherence, and the potential mediation of cognition on the relationship between adherence and weight loss in this group.